Harvesting and post-harvest management - Khan, A.; Singh, Zora (2017)
This chapter attempts to summarize briefly all the steps involved in harvesting and postharvest management of limes (Rutaceae), including harvesting, postharvest treatments, packing, storage and transportation, which can positively influence the fruit postharvest life and quality. The fruit maturity, grade standards and postharvest physiology are also discussed. Future prospects are given.